The Problems of Current Tourism and Hospitality Higher Education for Undergraduates in China - Zheng, Youli (2008)
The tourism industry has boomed within the last three decades. With the rapid development of the tourism industry in China, tourism and hospitality education, especially higher education, has also flourished in China. In 1978, not a single program was offered in tourism and hospitality education at any of the universities and colleges. However, in 2005 there were 693 universities and colleges offering tourism and hospitality programs and this number is still rapidly increasing. This dissertation will focus on tourism and hospitality higher education for undergraduates in China and gain an insight into the curriculum and whether it is effective in providing students who can adapt to the developing tourism industry, identify the problems with current tourism and hospitality undergraduate education in China and study how it can be improved in the future to adapt to the tourism industry. In order to obtain more vivid and detailed information, a mixed method approach consisting of both quantitative and qualitative surveys is used in the research process. According to the findings gained from the survey of students, teachers and managers, it can be seen that the current tourism and hospitality undergraduate education in China is not very effective in meeting the demands of the tourism industry and it still has some problems. In response to these problems, recommendations will be given in the final section.